2013
DOI: 10.1177/1470320313487567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin II blockade on cardiomyocyte regeneration after myocardial infarction in rats

Abstract: The number of newly formed cardiomyocytes increased after MI. Angiotensin II blockade neither stimulated nor prevented cardiomyocyte regeneration. ARB treatment increased vascular densities in the infarct border zone and modulated remodelling of the non-infarcted myocardium preventing effectively post-MI cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Although it is difficult to separate out the effect of Ang II on the satellite cell pool and its effect to reduce satellite cell proliferation and the relative contribution of each in vivo to the inhibition of regeneration, these data suggest that, in pathophysiological conditions of Ang II excess, normal muscle regenerative responses are blunted via an AT1R-mediated mechanism. It has been reported that AT1R blockers in LAD artery-ligated rodents have either no effect or modest effects on cardiac function (32)(33)(34)(35). Our data indicate that there was no significant improvement in cardiac function in response to candesartan in our experimental setting (Fig.…”
Section: Discussionmentioning
confidence: 46%
“…Although it is difficult to separate out the effect of Ang II on the satellite cell pool and its effect to reduce satellite cell proliferation and the relative contribution of each in vivo to the inhibition of regeneration, these data suggest that, in pathophysiological conditions of Ang II excess, normal muscle regenerative responses are blunted via an AT1R-mediated mechanism. It has been reported that AT1R blockers in LAD artery-ligated rodents have either no effect or modest effects on cardiac function (32)(33)(34)(35). Our data indicate that there was no significant improvement in cardiac function in response to candesartan in our experimental setting (Fig.…”
Section: Discussionmentioning
confidence: 46%
“…Importantly, these metabolic changes were associated with cardiomyocyte hypertrophy, rather than hyperplasia. RAS playing a role in cardiomyocyte proliferation is unlikely given that its inhibition was not found to mediate cardiomyocyte proliferation post-MI, but did increase vascular densities in the border zone [ 193 ]. Consistently, upregulation of AT1 was found to decrease microvessel densities in the setting of MI, while its inhibition promoted angiogenesis [ 194 , 195 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant increase in group III when compared to I and IV group. This could be explained by the study of [28] that the ameliorating effect of SCs over that produced by LOS and also documented that LOS neither stimulated nor prevented cardiomyocyte regeneration.…”
Section: Discussionmentioning
confidence: 99%